The European TeleCheck-AF project on remote app-based management of atrial fibrillation during the COVID-19 pandemic: centre and patient experiences. Issue 7 (2nd April 2021) - Gawałko, Monika; Duncker, David; Manninger, Martin; van der Velden, Rachel M.J.; Hermans, Astrid N.L.; Verhaert, Dominique V.M.; Pison, Laurent; Pisters, Ron; Hemels, Martin; Sultan, Arian; Steven, Daniel; Gupta, Dhiraj; et al.
Abstract: Aims: TeleCheck-AF is a multicentre international project initiated to maintain care delivery for patients with atrial fibrillation (AF) during COVID-19 through teleconsultations supported by an on-demand photoplethysmography-based heart rate and rhythm monitoring app (FibriCheck ® ). We describe the characteristics, inclusion rates, and experiences from participating centres according the TeleCheck-AF infrastructure as well as characteristics and experiences from recruited patients. Methods and results: Three surveys exploring centre characteristics ( n  = 25), centre experiences ( n  = 23), and patient experiences ( n  = 826) were completed. Self-reported patient characteristics were obtained from the app. Most centres were academic (64%) and specialized public cardiology/district hospitals (36%). Majority of the centres had AF outpatient clinics (64%) and only 36% had AF ablation clinics. The time required to start patient inclusion and total number of included patients in the project was comparable for centres experienced (56%) or inexperienced in mHealth use. Within 28 weeks, 1930 AF patients were recruited, mainly for remote AF control (31% of patients) and AF ablation follow-up (42%). Average inclusion rate was highest during the lockdown restrictions and reached a steady state at a lower level after easing the restrictions (188 vs. 52 weekly recruited patients). Majority (>80%) of the centres reported no problems during the implementation of the TeleCheck-AF approach. Recruited patients [median age 64 (55–71), 62% male] agreed that the FibriCheck ® app was easy to use (94%). Conclusion: Despite different health care settings and mobile health experiences, the TeleCheck-AF approach could be set up within an extremely short time and easily used in different European centres during COVID-19.